Visual Analysis on Photoacoustic Emission Images of Synthetic Dye Contrast Agents inside a Simple Closed-Surface Phantom - Mahendra Kusuma Nugraha; Ernawatil Gani; Mitrayana Mitrayana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
A straightforward photoacoustic microscopy imaging system utilizing a laser diode emitting photons at wavelength of 450 nanometers was employed for visualizing contrast-enhanced phantom objects. These phantoms consist of polypropylene tubes with a diameter of 0.3 cm, infused with three types of dye solutions: methylene blue, methyl orange, and methyl red, at varying concentrations of 10 ppm, 25 ppm, 50 ppm, and 100 ppm. In total, twelve phantom objects were imaged, each positioned over a 1x1 cm imaging area constructed from composite galvalume plates. A condenser microphone with audiosonic frequency response was employed as the photoacoustic detector, capturing ones generated by the objects. These emissions were subsequently processed and transformed into two-dimensional polychromatic images. Three primary aspects govern the visual characteristics of each acquired image: (i) the visible light absorption capacity at 450 nanometers for each type of dye; (ii) the concentration of soluble dye molecules; and (iii) the geometry and shape of the polypropylene tube functioning as the closed-surface phantom. It was discovered that utilizing polypropylene tubes as the closed-surface phantom can hinder the propagation of photoacoustic emissions generated by the solution, leading to significantly lower measured photoacoustic intensity than expected. When combined with the intrinsic properties of the contrast agents used, this key factor ultimately shapes the image features obtained from this experiment.